Perfil de pacientes portadores de hanseníase nas formas clínicas dimorfa e virchowiana atendidos em unidades de referência estadual em São Luís-MA - CASTRO, Williane Maria Menezes (2024)
Leprosy is an infectious, chronic disease, caused by a bacteria called Mycobaterium leprae, of a long-lasting nature, which stands out for remaining in the body for several years, affecting all age groups, of great importance for public health, due to its magnitude and its high disabling power. The present study aimed to analyze the socioeconomic and clinical profile of patients with leprosy in the dimorphic and lepromatous clinical forms in state leprosy reference units in São Luís (MA). This is a quantitative, descriptive, sectional research. The study was carried out at Hospital Aquiles Lisboa and Hospital Genésio Rêgo. The data collected was from the 12-month period between July 2022 and July 2023 through a form directly from the medical records and analyzed by the Power BI program, which analyzed data from 284 medical records relating to the research. Leprosy is present in 180 male patients, corresponding to 63.37%, and in female patients in 104 patients, corresponding to 36.63%, aged between 41 and 50 years, in relation to the brown ethnic group, in all age groups are above 65%. The occupation of farmer corresponded to 29.65%, and the most common clinical form was the dimorphic form with 63.38% who did not present adverse effects and the lepromatous clinical form 29.58%. Grade I, comprising 137 cases in the most present dimorphic clinical form with 30.28% and lepromatous form with 17.96%. In view of the results obtained, it was found that males are the most prevalent, aged between 41 and 50 years old, working as farmers and belonging to a brown ethnic group. The most common form of leprosy presentation was the dimorphic form and with grade 1 physical disability, with a higher prevalence in the age group from 51 to 60 years old with 9.86% and the number of nerves affected greater than 5 nerves, and more than 10 lesions at the time of diagnosis. Regarding the adverse effects of treatment, 63.38% of patients did not experience any type of drug reaction. Skin biopsy was not performed in 61.96% of cases, with BI 3 being the most common at 1.06%.